Investigation of a severe aflatoxicosis outbreak among chicken in Himachal Pradesh - CHAHOTA, RAJESH; KATOCH, R C; SINGH, S P; VERMA, SUBHASH; MAHAJAN, ARVIND; NAGAL, K B. (The Indian Journal of Animal Sciences, 2013)
A severe outbreak of aflatoxicosis among chickens in an organized poultry farm, which was complicated by secondary microbial invasion involving E.coli, Streptococcus Spp., Candida albicans etc., was investigated. The mortality percentage was 65,25,35 and 30 among broiler chicks (1-2 week of age), layer chicks (2-3 weeks of age), broilers (8 weeks of age) and adult broilers (14-15 weeks of age) respectively. The aflatoxin level in feeds given to different age groups varied from 100 ppb to 500 ppb. The corresponding pathological alterations in different visceral organs were encountered on histopathological investigation.